Peran Guru sebagai Pilar Utama dalam Pembentukkan Karakter Peserta Didik di Sekolah Menengah Pertama Madani Makassar: The Role of Teachers as the Main Pillar in Shaping the Character of Students at Madani Junior High School Makassar - Sona, Fitri; Rosdiana; Achruh, Andi (ISEDU : Islamic Education Journal, 2023)
In character education, students not only learn about theory and practice but students are invited to reach the cognitive aspect of "knowledge" and also touch the aspect of "behavior" by involving all aspects simultaneously and continuously. Teachers as role models are implementing discipline starting from themselves, which means that if the teacher behaves well, students will also imitate the good behavior of the teacher. Teachers must be able to set a good example to their students. The aim of this research is to determine the role, role models of teachers and factors in developing students' character. The method used is a qualitative research method, often called a naturalistic research method because the research is carried out in natural conditions (natural settings). This research uses a qualitative approach based on the phenomena that occur. The results of the research showed that not only talking but also doing deeds, because one example is better than a thousand words. If the teacher asks the child, he also needs to participate in it. The development of students' character is in the hands of teachers as educators and role models, because what teachers do is what students will imitate.